Collaboration, wealth and value creation, SMEs’ halal products communities, and information systems - Machfud, Alfi Khairiansyah; Ahmad Dahlan, Abdul Rahman; Khatib, Jawdat; Haji-Ahmed, Ahmed Abdulaziz (The Society of Digital Information and Wireless Communications, 2011)
This paper takes the form of a general review. It introduces the notion of government-industry collaboration and information sharing in the Halal industry that work together for achieving common goals such as in economic, health, environmental, and social well-being – moving towards making living more meaningful, productive, fruitful and profound. Technological empowerment – in particular inter-organizational information systems (IS) and information sharing – is regarded as the key driver for supporting a sustainable economic development at the global, regional and local levels. Through IS, it is viable and essential to establish a global knowledge base, shared, used, enhanced and contributed to by a variety of experts and professionals throughout the world in different fields toward achieving common goals.